Inactive mosques : The crisis of contemporary Muslim communities - Asif, Nayeem; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni (AENSI Publications, 2015)
According to the present conventional concept, mosque is only a place for the Muslims to offer prayer but in reality it should serve as a complex socio-cultural institution within the Muslim communities around the world. Though the contemporary evidences would go against this statement, it has to be noted that the original idea of mosque illustrates that it should be an institution that actively contributes to the development of the Muslim communities within the society. The aim of this paper is to explore the theological and historical evidences on mosque as an institution for community development. Then a brief overview will be presented on the contemporary issues i.e. the reason of the mosques being inactive nowadays and finally how to overcome this situation and revive the role of mosque in order to make it active again to contribute in the community development.